PERAN REGULASI EMOSI DAN KEBERMAKNAAN HIDUP TERHADAP KHUSYU BERIBADAH PADA PEREMPUAN YANG SUDAH MENIKAH - Maryatim, Sri; Alifa Asyafila Rahmadani (LPPM STAI Muhammadiyah Probolinggo, 2026)
Devout worship is a spiritual condition that is closely related to psychology. This is very important foe married women because of the heavy roles and demand of domestic life which can trigger a decline in the quality of worship. This research aims to see the extent of the role of emotional regulation end the meaningfulness of life on devotion to worship in married women. The research methods with convenience sampling techniques. Data collection was carried out using scales of emotional regulation, meaningfulness of life and devotion to worship which have been tested for validity and reliability. Data analysis was tasted using multiple regression analysis. The result of the study interpret that emotional regulation and the meaning of life. Simultaneously have a positive role in devotion to worship. The findings from the results of this research mean that the better women are at regulating their emotions, the easier it will be to find meaning in their lives, so that they can also increase devotion in worship.